2022
DOI: 10.1007/s00134-022-06650-z
|View full text |Cite
|
Sign up to set email alerts
|

Natural language processing diagnosed behavioral disturbance vs confusion assessment method for the intensive care unit: prevalence, patient characteristics, overlap, and association with treatment and outcome

Abstract: Purpose: To compare the prevalence, characteristics, drug treatment for delirium, and outcomes of patients with Natural Language Processing (NLP) diagnosed behavioral disturbance (NLP-Dx-BD) vs Confusion Assessment Method for intensive care unit (CAM-ICU) positivity. Methods:In three combined medical-surgical ICUs, we obtained data on demographics, treatment with antipsychotic medications, and outcomes. We applied NLP to caregiver progress notes to diagnose behavioral disturbance and analyzed simultaneous CAM-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…We analysed these notes using NLP techniques. As previously described [ 8 , 15 ], each progress note was converted into sentence vectors, tokenised and searched for the presence of words indicative of agitated or non-agitated behaviour (Natural Language Toolkit; NLTK 3.5) [ 16 ], a process equivalent to the first step of Large Language Model Generative Pre-trained Transformer strategies recently popularised by OpenAI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We analysed these notes using NLP techniques. As previously described [ 8 , 15 ], each progress note was converted into sentence vectors, tokenised and searched for the presence of words indicative of agitated or non-agitated behaviour (Natural Language Toolkit; NLTK 3.5) [ 16 ], a process equivalent to the first step of Large Language Model Generative Pre-trained Transformer strategies recently popularised by OpenAI.…”
Section: Methodsmentioning
confidence: 99%
“…Such studies have also suggested that there might be clinical value in further investigating the characteristics, prevalence, trajectory, treatment, and outcomes of disturbed behavioural phenotypes, a similar but not identical concept to delirium [ 8 14 ]. In this regard, natural language processing (NLP) of caregivers’ notes has recently emerged as a screening tool for behaviour in critically ill patients [ 8 14 ]. NLP has also been recently used to describe the syndrome of NLP-diagnosed behaviour disturbance (NLP-Dx-BD) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of ED, NLP has demonstrated that neither ICD codes or specific delirium clinical scales are sensitive enough to capture all the phenotypic range of encephalopathy. In particular, behavioural disturbances captured by NLP encloses more patients at risk of receiving antipsychotic medications or having higher morbimortality rates in the ICU than the group of patients defined by the CAM-ICU ( 17 ). Recent approaches have tried to incorporate keywords related to the delirium semiology into machine learning classifiers to label patients with delirium ( 10 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Intensive Care Medicine [ 12 ], Young and colleagues present study results from an ICU cohort evaluated twice daily with the CAM-ICU. In parallel, behavioral disturbances were identified with natural language processing (NLP) using 24 previously validated words documented in ICU chart notes.…”
mentioning
confidence: 99%